Performance Effectiveness of Natural Science Using Productive Assessment Instruments at PGSD FKIP UNTAN - Sabri, Tahmid (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2018)
This research started from "whether effective learning performance of Natural Sciences student using productive assessment instrument in PGSD FKIP Untan Pontianak?". This study aims to get a picture of the effectiveness of the performance of Natural Science Learning using productive assessment instruments in PGSD (Primary School Teacher Education). The method used is descriptive with a qualitative approach in the form of class research. The results obtained turns out when compared with the learning of Natural Sciences without using instruments of productive assessment, activity and result of students in learning have increased significantly. The hope of this research results can contribute to the improvement of the quality of natural science learning in PGSD which has implications on the acquisition of student learning in elementary school.